Elementary School Students' Behavior Towards Memorizing The Quran During The Covid 19 Pandemic - Rifki Zaitul Ikhlas; Abdillah Rofiif Fatin Ritonga; Muhammad Hanif (Yayasan Adra Karima Hubbi, 2024)
Background. The COVID-19 pandemic has disrupted various aspects of life, including education. The Padang city mosque imam cadre school applies face-to-face and compulsory boarding methods of memorizing the Quran to overcome the limitations of physical interaction. Purpose. This study aims to understand the behavior of elementary school students towards memorizing the Quran during the COVID-19 pandemic and identify the challenges faced. Method. This research uses a descriptive method with a qualitative approach. Data was collected through interviews, observation, and documentation. The subjects of the study included principals and teachers at the mosque imam cadre school in the city of Padang. Results. The results showed that despite the limitations due to the pandemic, students remained enthusiastic in memorizing the Quran. The face-to-face use of wahdah methods and living in dormitories help students maintain their memorization. However, students' motivations vary and some students show a decrease in enthusiasm in memorizing the Quran. Conclusion. The COVID-19 pandemic has affected students' behavior in memorizing the Quran. Nonetheless, with proper support and supervision from teachers and living in dormitories, students can maintain their memorization. It takes constant motivation and support from the surrounding environment to keep students' enthusiasm in memorizing the Quran.